2014
DOI: 10.4103/0974-2700.136847
|View full text |Cite
|
Sign up to set email alerts
|

Acute Flaccid paralysis in adults: Our experience

Abstract: Acute flaccid paralysis (AFP) is a complex clinical syndrome with a broad array of potential etiologies that vary with age. We present our experience of acute onset lower motor neuron paralysis.Materials and Methods:One hundred and thirty-three consecutive adult patients presenting with weakness of duration less than four weeks over 12 months period were enrolled. Detailed history, clinical examination, and relevant investigations according to a pre-defined diagnostic algorithm were carried out. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Incidence of MFS is often less frequently reported in previous studies [23,24], as no MFS patients were reported during our study period. and descending pattern of weakness in 6.8% [15]. Facial palsy was seen in more than half of the GBS patients and bilateral weakness pattern was seen in most of them which was consistent with previous studies [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Incidence of MFS is often less frequently reported in previous studies [23,24], as no MFS patients were reported during our study period. and descending pattern of weakness in 6.8% [15]. Facial palsy was seen in more than half of the GBS patients and bilateral weakness pattern was seen in most of them which was consistent with previous studies [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed men are more likely to have GBS than women which was consistent with most of the GBS studies [14][15][16]. GBS can affect people of all ages, but majority of patients were below the age of 40 years.…”
Section: Discussionsupporting
confidence: 90%
“…Neuroparalytic snakebite has been previously reported as a significant cause of acute flaccid paralysis in young rural men from Northern India. [2] Our study shows a male preponderance among patients with acute flaccid paralysis Males constituted 69/97 (71.1%) of total number of cases. This is attributed to higher proportion of males in both snake envenomation and LGBS groups.…”
Section: Discussionmentioning
confidence: 50%
“…AIP as cause of AFP was noted in 4.5% patients. [ 17 ] In a descriptive observational study, among 108 patients presenting with features of acute polyneuropathy or encephalopathy associated with pain and/or dysautonomia, porphyrin metabolites were screened. AIP was diagnosed in 12 patients.…”
Section: Discussionmentioning
confidence: 99%